Conversion of lipid biomass to liquid hydrocarbons via pericyclic decarboxylations of α,β- and β,γ-unsaturated fatty acids using polycyclic aromatic hydrocarbon (PAH) solvent systems - Romanishan, Michelle, author; Crans, Debbie C., advisor; Henry, Charles S., committee member; Barisas, George, committee member; Van Orden, Alan, committee member; Reardon, Kenneth, committee member (Colorado State University. Libraries, 2014)
Development of a new process for converting lipid biomass, containing α,β- and β,γ-unsaturated fatty acids, to liquid hydrocarbon fuels (LHF) of varying carbon number is described in this dissertation. The theme for LHF production at present revolves around utilizing a catalytic system that requires high temperatures and pressures as well as multiple processing steps. The cost attributed to these types of processes has been a hindrance in moving the economy towards a cost-effective renewable fuel. Investigating possible catalyst-free processing techniques has led to the discovery of a lower energy reaction that utilizes specific unsaturated fatty acids into a cheap, high boiling point solvent system that has the ability to produce pure alkenes as liquid hydrocarbon fuels when heated to reflux temperature of the fatty acid. This sustainable process has been proven to decarboxylate α,β- and β,γ-unsaturated fatty acids via a pericyclic rearrangement. Using a high boiling, polycyclic aromatic hydrocarbon (PAH) solvent, such as phenanthrene or pyrene, pure alkene products in high yields have been obtained from heating α,β- or β,γ-unsaturated fatty acids to a temperature no higher than reflux of the acid. The successful process development and subsequent conversion of lipid-like biomass will be discussed at length and confirmed by ¹H NMR and GC/MS.
Keywords: α,β- and β,γ-unsaturated fatty acids; pericyclic decarboxylations; renewable energy; renewable fuel processing; alkenes; liquid hydrocarbon fuel